Occupation-focussed practice in justice health and forensic mental health: Using a practice-based enquiry approach. Issue 2 (October 2015) - Perkes, Danielle; Whiteford, Gail; Charlesworth, Glen; Weekes, Gemma; Jones, Katherine; Brindle, Sophia; Hoare, Linda; Todd, Emma; Ray, Mililani
Abstract : Providing occupational therapy services in secure settings can be challenging due to a number of factors including, but not restricted to, the limitations of the physical environment. Maintaining an occupation focus in such environments can also be difficult, especially if there are competing institutional philosophies. In this article, we describe a project undertaken by a group of occupational therapists in NSW, Australia which focuses on centralising occupation in the programmes they provide in a number of units within state funded Justice and Forensic Mental Health Services. The project utilises a practice-based enquiry approach through which the practitioners engage in a reflective analysis of their everyday practices and the artefacts produced in practice. Collectively, the group of practitioners together with an academic have formed a community of practice scholars who both critique and support each other's enquiry processes and actions aimed at transforming practice. Whilst the project is only in its early stages at the time of writing, it is hoped that the findings will inform other occupational therapists hoping to 'reclaim occupation' in their practice setting.